Syntheses of nanoparticles by wire explosion technique / Lee Yen Sian - Lee, Yen Sian (2012)
Nanoparticles generally refer to particles with sizes less than 100 nm. They exhibit distinguished properties compared to their bulk form due to their small size and high surface-to-volume ratio. Various methods have been developed to fabricate such particles where wire explosion technique is one of them. In brief, wire explosion is realized by allowing a high power pulsed current to pass through a thin wire. The current will provide the energy to vaporize the wire due to the Joule heating effect. The formation of nanoparticles starts when the vaporized wire forms a supersaturated vapour that is followed by nucleation of vapour particles. Subsequent growth of the nuclei will lead to formation of nano-sized particles. In this work, we had investigated the effect of ambient gas and pressure on the characteristics of nanoparticles synthesized by the wire explosion technique. Copper wires 125 μm in diameter with a length of 6.1 cm had been exploded with current supplied by a 1.85 μF capacitor being charged up to 10 kV. In order to investigate the effect of the ambient gas on the characteristics of nanoparticles being produced, copper wires were exploded in ambient gas of nitrogen, argon and nitrogen-argon admixtures at a pressure of 500 mbar. Meanwhile, study on the effect of ambient gas pressure had been conducted by exploding the copper wires in air and nitrogen ambient at 1 bar, 500 mbar, 100 mbar and 50 mbar. The size of the particles had been evaluated by transmission electron microscope (TEM) while the crystalline structure of the particles was examined by using X-ray diffraction (XRD) method.